Hospital Practice of Direct‐Home Discharge and 30‐Day Readmission After Transcatheter Aortic Valve Replacement in the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy (STS/ACC TVT) Registry. Issue 8 (August 2017) - Dodson, John A.; Williams, Mathew R.; Cohen, David J.; Manandhar, Pratik; Vemulapalli, Sreekanth; Blaum, Caroline; Zhong, Hua; Rumsfeld, John S.; Hochman, Judith S.
Abstract : Background: Nearly 17% of patients are readmitted within 30 days of discharge after transcatheter aortic valve replacement. Selected patients are discharged to skilled nursing facilities, yet the association between a hospital's practice to discharge home versus to skilled nursing facilities, and readmission remains unclear. Methods and Results: The Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy (STS/ACC TVT) Registry was used to evaluate readmissions among patients undergoing transcatheter aortic valve replacement (2011‐2015). Hospitals were divided into quartiles (Q1‐Q4) based on the percentage of patients discharged directly home. We assessed patient and hospital level characteristics and used hierarchical logistic regression to analyze the association of discharge disposition with 30‐day readmission. Our cohort included 18 568 transcatheter aortic valve replacement patients at 329 US hospitals, of whom 69% were discharged directly home. Hospitals in the highest quartile of direct home discharge (Q4) compared with hospitals in the lowest (Q1) were more likely to use femoral access (75.2% versus 60.1%, P <0.001), had fewer patients receiving transfusion (26.4% versus 40.9%, P <0.001), and were more likely to be located in the Southern United States (48.8% versus 18.3%, P <0.001). Median 30‐day readmission rate was 17.9%. There was no significant difference in 30‐day readmissions among quartiles ( P =0.14), even after multivariable adjustment (odds ratio Q4 versus Q1=0.89, 95%CI 0.76‐1.04; P =0.15). Factors most strongly associated with 30‐day readmission were glomerular filtration rate, in‐hospital stroke or transient ischemic attack, and nonfemoral access. Conclusions: There was no statistically significant association between hospital practice of direct home discharge post–transcatheter aortic valve replacement and 30‐day readmission. Further research is needed to understand regional variations and optimum strategies for postdischarge care.